Holmium versus thulium laser enucleation of the prostate: a systematic review and meta-analysis of randomized controlled trials : review : a benign prostatic enlargement - Hartung, Friedrich; Kowalewski, Karl-Friedrich; Hardenberg, Jost von; Worst, Thomas; Kriegmair, Maximilian; Nuhn, Philipp; Herrmann, Thomas R. W.; Michel, Maurice Stephan; Herrmann, Jonas (European urology focus, 2022)
Context - Holmium (HoLEP) and thulium laser enucleation of the prostate (ThuLEP) are the two methods most commonly applied for endoscopic enucleation of the prostate. It remains unclear which of the two is superior in terms of outcome and complications. - Objective - To compare perioperative and functional outcomes between HoLEP and ThuLEP. - Evidence acquisition - A systematic review and meta-analysis were performed according to the recommendations of the Cochrane Collaboration and in line with the PRISMA criteria. A comprehensive database search including MEDLINE, Web of Science, CINAHL, ClinicalTrials.gov, and CENTRAL was conducted according to the PICO criteria. Only randomized controlled trials (RCTs) were considered. All review steps were conducted by two independent reviewers. Risk of bias was assessed using the revised Cochrane tool for RCTs. - Evidence synthesis - The search identified 556 studies, of which four were eligible for qualitative and quantitative analysis, reporting on a total of 579 patients with follow-up of up to 18 months. No significant differences in operating time, enucleation weight, catheterization time, or hospital stay were observed between ThuLEP and HoLEP. The decrease in hemoglobin was significantly lower for ThuLEP (mean difference −0.54 g/dl, 95% confidence interval [CI] −0.93 to −0.15; p < 0.001), but with low certainty of evidence. Transient urinary incontinence was more common for HoLEP (odds ratio 0.56, 95% CI 0.32-0.99; p = 0.045), again with low certainty of evidence. Furthermore, no significant differences were observed for other complications or for functional measures and symptom scores. - Conclusions - ThuLEP and HoLEP offer comparable improvement in symptoms and postoperative voiding parameters. Both procedures are safe and major complications are rare. ThuLEP showed minor advantages for blood loss and the incidence of transient incontinence. This should be interpreted with caution owing to the low certainty of evidence. Therefore, treatment choice should be based on surgeon expertise and local conditions. - Patient summary - We reviewed four clinical trials that compared holmium and thulium lasers for treatment to reduce the size of the prostate gland. Our review assessed outcomes and complications. We found that both laser techniques are safe and suitable for reducing symptoms due to an enlarged prostate. Blood loss and short-lasting urinary incontinence were slightly lower after thulium compared to holmium laser treatment.
Online verfügbar: 8. April 2021, Artikelversion: 2. Juni 2022
Gesehen am 23.04.2024